Financial development and income inequality in emerging markets: A new approach - Thang Cong Nguyen; Tan Ngoc Vu; Duc Hong Vo; Dao Thi-Thieu Ha (Journal of Risk and Financial Management, 2019)
Financial development has been considered an efficient and effective mechanism for the sustainable economic growth and development of emerging markets in past decades. However, various concerns have emerged in relation to the influences of financial sector development on income inequality. It is the claim of this paper that findings from the current literature are incomplete. This is because various proxies have been utilized inconsistently for both financial development and income inequality in previous empirical studies. This study extends the current literature on this important finance–inequality nexus by examining a sample of 21 emerging countries for the period of 1961-2017. Various estimation techniques were employed with the aim of ensuring robust findings. Findings from this paper confirm the existence of an inverted U-curve relationship between financial development and income inequality, implying that income inequality may rise at the early stage of financial development and fall after a certain level is achieved. Policy implications have emerged from the findings of this study.
Keywords: 330; DOLS; emerging markets; financial development; FMOLS; income inequality